2016
DOI: 10.1093/carcin/bgw018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the CIMP-like subtype and aberrant methylation of members of the chromosomal segregation and spindle assembly pathways in esophageal adenocarcinoma

Abstract: SummaryThis study describes the esophageal cancer methylation landscape and its impact on gene expression. Genes aberrantly methylated suggest a mechanism that could lead to genomic instability and chromothripsis. A CpG island methylator phenotype-like subtype with potentially worse clinical outcome was also identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 50 publications
5
58
0
Order By: Relevance
“…While the distributions are similar for BE and EAC, EAC show more advanced drift in the third group (bimodal high) which may be attributed to EAC patients being on average older than the BE patients (68 vs 62 years, respectively), or to the fact that EAC undergoes more frequent stem cell divisions thereby increasing replication-coupled de novo methylation, or to the possibility that BE arises earlier in patients with EAC compared to patients who have not progressed to dysplasia or EAC. We found similar unimodal/bimodal drift signatures in 87 EAC from TCGA and in a combined set of 19 BE and 47 EAC tissue samples provided by Krause et al [ 16 ] (GEO accession number: GSE72874).
Fig.
…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…While the distributions are similar for BE and EAC, EAC show more advanced drift in the third group (bimodal high) which may be attributed to EAC patients being on average older than the BE patients (68 vs 62 years, respectively), or to the fact that EAC undergoes more frequent stem cell divisions thereby increasing replication-coupled de novo methylation, or to the possibility that BE arises earlier in patients with EAC compared to patients who have not progressed to dysplasia or EAC. We found similar unimodal/bimodal drift signatures in 87 EAC from TCGA and in a combined set of 19 BE and 47 EAC tissue samples provided by Krause et al [ 16 ] (GEO accession number: GSE72874).
Fig.
…”
Section: Resultssupporting
confidence: 73%
“…In total, we identified 200 genes that were significantly underexpressed in the advanced drift group while only 10 genes were significantly overexpressed (Additional file 2 : Table S1). Independently, we found 35 genes that were significantly repressed and none that were significantly overexpressed among 51 (47 EAC + 4 BE) samples provided by Krause et al [ 16 ]. Importantly, several genes (20/35) that were found repressed in the smaller study by Krause et al were also found repressed in TCGA (Additional file 2 : Table S1).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, close clustering of BE and EAC tissues suggested key methylation events to occur early during the progression of EAC . Another study determining the methylation landscape of EAC and its impact on gene expression identified distinct methylation patterns pertaining to subtypes of EAC, one similar to the CpG island methylator phenotype that was potentially associated with a worse clinical outcome . Apart from widespread hypermethylation of genes, global hypomethylation was found to be an early event in EAC development, even observed within the first visible metaplastic lesions of the squamous esophagus .…”
Section: Epigenomics Of Ecmentioning
confidence: 99%
“…97 Another study determining the methylation landscape of EAC and its impact on gene expression identified distinct methylation patterns pertaining to subtypes of EAC, one similar to the CpG island methylator phenotype that was potentially associated with a worse clinical outcome. 99 Apart from widespread hypermethylation of genes, global hypomethylation was found to be an early event in EAC development, even observed within the first visible metaplastic lesions of the squamous esophagus. 100,101 Hypomethylation has been hypothesized to lead to carcinogenesis by encouraging genomic instability, aberrant activation of oncogenes, or transcriptional upregulation during multistep progression to high-grade dysplasia and cancer.…”
Section: Tumor-specific Dna Methylation Tumor-specific Dna Methylatiomentioning
confidence: 99%